Real Time Image Processing for Object Detection - Mednieks, I.; Skageris, A. (Elektronika ir Elektrotechnika, 2009)
A device implementing fast processing of grayscale images is described, capable of detecting small foreign bodies in images of controlled objects and proposed for industrial inspection (e.g. of food products) systems exploiting modern image detectors featuring high resolution and scanning speed. Exploited methods and structure of the device are optimized for use in real time mode and suitable for implementation on the basis of FPGA technology. Ill. 7, bibl. 11 (in English; summaries in English, Russian and Lithuanian).